Association of Wilms tumor-1 protein in urinary exosomes with kidney injury: a population-based cross-sectional study - Khandpur, Sukhanshi; Srivastava, Medha; Sharma, Rajni; Asif, Shafaque; Bhadauria, Dharmendra S.; Mishra, Prabhaker; Purty, Anil J.; Tiwari, Swasti (Frontiers in Medicine, 2023)
Objective: Loss of Wilms tumor-1(WT1) protein, a podocytopathy marker, through urine exosome (uE) could be an early indication of kidney injury. We examined WT1 in uE (uE-WT1), along with other urine markers of glomerular and kidney tubule injury, in individuals without chronic kidney disease (CKD).The cross-sectional study included individuals who reported to have no evidence of chronic kidney disease (CKD). Albumin-to-creatinine ratio (ACR) and estimated glomerular filtration rate (eGFR) were used to assess kidney function. eGFR was calculated using 2009 CKD-EPI (CKD-Epidemiological) equation. WT1 was analyzed in uE from humans and Wistar rats (before and after 9 th week of diabetes, n=20). uE-WT1, urinary Neutrophil gelatinaseassociated lipocalin (NGAL) and Kidney injury molecule-1(KIM-1) were estimated by ELISA.Kruskal Wallis H test, Mann-Whitney U test, and Stepwise multivariable linear regression were performedUrine NGAL and ACR increases with uE-WT1 quartiles, (n=146/quarter). Similarly, uE-WT1, KIM-1 and NGAL was positively associated with ACR. Further, KIM-1, NGAL and uE-WT1 correlated with ACR. uE-WT1 outperformed KMI-1 and NGAL to explain ACR variability(25% versus 6% or 9%, respectively). Kidney injury in streptozotocin-induced diabetic rats was associated with a significant rise in uE-WT1. Moreover, the findings were confirmed by histopathology of kidney tissues from rats.Conclusion: uE-WT1 was strongly associated with kidney function in rats. In individuals without CKD, uE-WT1 outperformed NGAL as a determinant of differences in ACR.